E EFEKTVITAS TERAPI AIR PUTIH TERHADAP KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 STUDI: NARRATIVE REVIEW - Noor Hikmah; Rian Tasalim; Onieqie Ayu Dhea Manto (LPPM Universitas Sari Mulia, 2021)
Background: Diabetes mellitus is a disease characterized by high blood sugar. One way to control the increase in blood sugar in patients with diabetes mellitus is hydrotherapy. This therapy can help break down sugar in the blood and remove toxins through sweat and urine.The purpose of this study to analyze the effectiveness of hydrotherapy with sugar levels in patients with diabetes mellitus. Method: Narrative review research design. The journal criteria used were filtered based on the literature title, abstract and keywords or keywords, namely hydrotherapy, sugar levels, diabetes mellitus. Results: Journal studies show that drinking hydroherapy is effective in reducing blood sugar levels in patients diabetes mellitus type 2. Conclusion: Narrative can increase the knowledge of diabetes mellitus patients by providing information about the benefits of consuming sufficient water as complementary therapy.